Human Resources Management Strategy in Improving the Quality of Employee Performance of PT JNT Express - Fadhil Heryanto; Juliani Juliani; Putri Nadia Mahar Arini; Rian Ramahdani; Satriadi Satriadi (Dinasti International Journal of Education Management And Social Science, 2024)
This study aims to analyze the Human Resources Management Strategy in Improving the Quality of Employee Performance of PT JNT Express on Jl. RH Fisabilillah Depan Kopi Tiam. This research uses a qualitative approach with a descriptive design. The research subject was determined by purposive technique. Data collection using interview and observation techniques. Data validation using source triangulation techniques. While data analysis uses descriptive model techniques. The results showed that the good performance of employees despite the limited number. With collaboration between administrative employees and couriers, they can complete important tasks such as packing and arranging goods receipts.